Harihareshwari-013 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Although the lute in the Goddess's hand suggests Saraswati, the other hands do not carry the traditional objects such as the book, japamala (garland), and a pot of water. Instead, the top right hand appears to carry a damaru - a small drum (symbolic with Shiva) and the top left hand a conch shell (symbolic with Vishnu.)